A Study to Assess the Effectiveness of Information Booklet on Knowledge of Mothers Regarding Prevention of Home Accidents among Children Under Five Years in Selected Urban Community Areas of Udaipur - RAWAT, VIJAY SINGH (Asian Journal of Pharmaceutical Research and Development, 2019)
Students are subjected to different kinds of stressors, such as the pressure of academics with an obligation to succeed, an uncertain future, and difficulties of integrating into the system. Aim: A descriptive study was conducted in selected nursing institutes of Udaipur to assess stress level and coping strategies among nursing students. A total of 100 students of B.Sc. Nursing first year participated in the study. Likert scale was used to assess stress level. Results: Results revealed that 4% of the samples had severe anxiety, 40% had moderate anxiety, 48% had mild anxiety, and 8% of samples have no anxiety. Anxiety levels were significantly higher in females in comparison to males (30.79±7.47 vs. 28.65±7.98; P = 0.036). Coping behavior was comparable in females in comparison to males (53.70±4.62 vs. 53.29±4.40; P = 0.768). Conclusion: Strengthening nursing students’ positive coping skills may be helpful for them to effectively deal with various stressors during their educational experiences while maximizing learning. Implementing empirically tested approaches may be useful to prevent the recurrence of stress and lessen its impact such as stress management counseling, counseling programs, establishing peer and family support systems, and formulating hospital policies that will support nursing students.